2016
DOI: 10.1080/13811118.2016.1224990
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Depression, Positive Symptoms of Psychosis, and Suicidal Ideation Among Adults Diagnosed With Schizophrenia Within the Clinical Antipsychotic Trials of Intervention Effectiveness

Abstract: Suicide is among leading causes of death for adults diagnosed with schizophrenia. While symptoms of depression are consistently supported factors involved in suicidal ideation, findings on the role of positive symptoms of psychosis have been mixed with limited understandings of risk. Accordingly, this study aimed to identify the pathways of influence between symptoms of depression, positive symptoms of psychosis (i.e. hallucinations and delusions), and suicidal ideation. Data were obtained from the Clinical An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Specifically, hallucinations and delusions play an important role in suicidal ideation (Bornheimer and Jaccard, 2016). Although there have been mixed findings with respect to positive symptoms affecting suicidal behavior, several authors opined that hallucinations predicted suicidal plans and ideation (Kjelbyet al, 2015), (Bertelsen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, hallucinations and delusions play an important role in suicidal ideation (Bornheimer and Jaccard, 2016). Although there have been mixed findings with respect to positive symptoms affecting suicidal behavior, several authors opined that hallucinations predicted suicidal plans and ideation (Kjelbyet al, 2015), (Bertelsen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The Positive and Negative Syndrome Scale (PANSS) was employed to find whether there is a connection between suicide attempt and psychotic symptom in patients with MDD or not, because the independent increase of positive symptoms of psychosis as well as the symptoms of depression can lead to the increase of suicidal ideation [28,29]. Each item is scored on a 7-point scale based on the level of psychopathology.…”
Section: Collection and Evaluation Of Socio-demographic And Clinical mentioning
confidence: 99%
“…Each item is scored on a 7-point scale based on the level of psychopathology. In this study, patients with a total positive symptom subscale score reaching or exceeding 15 were defined as having psychotic symptoms [29,30].…”
Section: Collection and Evaluation Of Socio-demographic And Clinical mentioning
confidence: 99%
“…In recent years, there have been mixed findings on whether the positive symptoms of schizophrenia contribute to the increased risk of suicide. Several studies have shown that the risk for suicide in patients with schizophrenia is significantly associated with the presence of psychotic symptoms, including delusions and hallucinations (Bertelsen et al, 2007;Bornheimer, 2016;Bornheimer & Jaccard, 2016;Nordentoft et al, 2002;Tarrier et al, 2006;Taylor et al, 2010), though this is not always the case (Hawton et al, 2005;Verdoux et al, 2001;Walsh et al, 2001). Since experiences of delusions and hallucinations may serve as a specific risk factor for suicide in affected individuals, recently developed psychological models of suicide have attempted to incorporate the impact of positive psychotic symptoms on the mind underlying suicidal ideation (Bolton, Gooding, Kapur, Barrowclough, & Tarrier, 2007;Bornheimer & Nguyen, 2016;Johnson, Gooding, & Tarrier, 2008).…”
Section: Introductionmentioning
confidence: 99%